ANALYSIS OF PESTICIDE RESIDUES IN POTATO PLANTS IN MOAT DISTRICT, EAST BOLAANG MONGONDOW REGENCY, INDONESIA - Riviani Yubelin Rompas; Orbanus Naharia; Masje Wurarah (Indonesian Biodiversity Journal, 2023)
The use of pesticides on highland vegetable crops by farmers is considered highly intensive. This is primarily due to favorable climatic conditions for developing plant pests and diseases. Pesticides are toxic bioactive chemical substances (at concentrations > 0.5 ppm). Each of these poisons carries risks to the environment and humans in their use. Pesticide residues are specific substances found in agricultural food crops or animal feed, either as a direct or indirect result of pesticide use. This research aims to determine the presence of pesticide residues in potatoes cultivated by the community of Moat Subdistrict, East Bolaang Mongondow Regency. This study adopts a qualitative descriptive approach with laboratory experimentation. Representative samples were taken from ten potato plantations in Moat Subdistrict, East Bolaang Mongondow villages. They were then analyzed at the Laboratory of Plant Protection and Quality Testing. Based on the research findings, the researchers concluded that six locations of potato tubers in 10 villages in Moat Subdistrict, East Bolaang Mongondow Regency, did not contain pesticides. In comparison, the remaining four locations showed pesticide content.